Solid-state synthesis of single-phase nickel monophosphosulfide for the oxygen evolution reaction. Issue 37 (24th August 2021) - Wang, Miao; Saad, Ali; Li, Xiaoguang; Peng, Tao; Zhang, Qi-Tao; Kumar, Mohan; Zhao, Wei
Abstract : A novel ternary NiPS compound with superior electrocatalytic OER activity fabricated via a simple solid-state route in alkaline media. Abstract : High-performance and cost-effective nonprecious-metal catalysts are essential for the next-generation oxygen evolution reaction (OER). However, the electrocatalysis of the OER during water splitting is often carried out by using noble metal catalysts, such as RuO2 or IrO2 with high-cost and limited stability. Herein, we reported a successful synthesis of a ternary nickel monophosphosulfide (NiPS) compound via a simple solid-state route and further investigated its electrocatalytic performances for water oxidation. It is found that the NiPS electrocatalyst exhibits good OER performance in 1.0 M KOH solution, i.e., achieving a current density of 20 mA cm −2 at an overpotential of 400 mV and a Tafel slope of 126 mV dec −1, comparable to commercial benchmark RuO2 . The ternary NiPS electrocatalyst for the OER is superior to its binary counterparts, i.e., Ni2 P and NiS. Density functional theory (DFT) calculations combined with ex situ XPS were performed to obtain further insights into the intrinsic catalytic mechanism of NiPS, and their results clearly revealed that the instability of the NiO intermediate during the OH* → O* process and the easy oxidation of the (PS) 3− anion favoring the formation of hydroxyl-based species ( i.e., Ni(OH)2 /NiOOH) on the surface of the catalyst, which plays a crucial role in facilitating the OER activity. Furthermore, we creatively extended this method to the fabrication of heteroatom substituted catalysts and a new quaternary CoNiP2 S2 compound was successfully synthesized for the first time in the same way. The structural properties and electrocatalytic performance towards the OER for CoNiP2 S2 ( e.g., 20 mA cm −2 at 376 mV) are also systematically investigated in this work.